Screening and characterization of Phosphorus solubilizing Bacteria and their effect on Rice seedlings (Research in Agriculture Livestock and Fisheries, 2015)
An experiment was carried out to isolate, screen and characterize bacteria collected from an industrially polluted site of Bhaluka under the Mymensingh district and to evaluate their phosphorus (P) solubilizing capacity. About ten plant and soil samples from six different spots were collected from the site. Thirty four bacterial isolates were screened and pure cultures of the different bacterial isolates were prepared. Among the bacterial isolates 25 were gram negative and 9 were gram positive. About 31 bacterial isolates had catalase producing capacity and remaining 3 were negative to catalase test. Bacterial isolates were grown on a NBRIP media to determine their phosphorus solubilizing capacity. About 25 bacterial isolates were shown P solubilizing capacity. Isolate SB8 gave the highest result about 11.42 PSI (phosphorus solubilizing index), whereas other bacterial isolates showed moderate P solubilizing capacity (PSI 1.75-6.35). A plant trial with selected isolates (SB8, SB15, SB25) were also done and SB8 achieved 10% higher P content in comparison with control which supports the in vitro P solubilization assays. DOI: http://dx.doi.org/10.3329/ralf.v1i1.22353 Res. Agric., Livest. Fish.1(1): 27-35, Dec 2014